(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Мақала авторы «Имир Гөроғли» атты халық дастаны мысалында ұйғыр фольклориндегі хронотоп мəселесін қарастырады. Ол халық дастандарында кейіпкер басып өткен жолды, алыстықты жырлауда уақыт көрсеткіш- терімен (сағат, күн, ай, жыл) жіи пайдаланатын айта өтіп, солай ақ халық метрологиясында қолданатын тұралы пікір айтады. Author considers problem of chronotopos in Uyghur folklore particularly on example of dastan “Imir Gorogli”. In this article researcher uncover temporal measurements in Uyghur dastans. This temporal measurements (a hour, a day, a day and night, year etc.) used by narrators in dastans for translation of continuance a way and length. Also in dastans narrators used meanings of folk metrology.